Ground reaction force and kinematics of forehand jumping smash among elite malaysian badminton players - Ramasamy, Y.; Usman, J.; Sundar, V (ISBS Proceedings Archive (Michigan), 2019)
This study identified the contribution of lower and upper extremity biomechanical parameters towards high velocity and accuracy of the shuttle in forehand straight jumping smash. A total of 19 Malaysian elite badminton players performed a forehand straight jumping smash to a designated area at the opposite area of the court.Multiple corelation test was performed to determine the contributions of each variable in all three phases.Maximal Ground Reaction force (r=.548,p< 0.05), Maximum jump height (r=.0505, r<0.05),Wrist angular velocity during back swing phase to contact phase (r=0.745,p<0.05) and Racket head speed(r=0.724,p<0.05). Wrist angular velocity of the racket hand shows the highest correlation followed by racket head speed during back swing phase to contact phase. Higher jumping height with shorter time duration will emphatically produce higher shuttle velocity and accuracy.